Mathematical Creative Thinking and Student Self-Confidence in the Challenge-Based Learning Approach - Hayatun Nufus; M. Duskri; Bahrun Bahrun (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2018)
The new curriculum (K13) requires a teacher to develop students’ ability in order to learn and fully understand Mathematics. The important abilities needed for a student in understanding Mathematics are the creative thinking and self-confidence. The certain study is essential in order to enhance students’ ability of mathematical creative thinking and self-confidence. Challenge-Based Learning is not only demanding a student to discover a solution to a problem, but also to be confident in what he has done. The qualitative method is used in this research to describe the students’ mathematical creative thinking ability and self-confidence. The subjects are six students chosen from 21 students of seventh grade at one of Junior High Schools in Aceh, Indonesia. They are the student with high, moderate, and low creative thinking ability. The research instrument is a test for creative thinking ability, a questionnaire of self-confidence and an interview guideline. The result indicates that the students with high and moderate level meet at least three indicators of creative thinking ability. They are also confident in solving the problem. In contrast, the student with low level did not reach any indicators of creative thinking ability and have poor self-confidence.